Trajectory of radiographic change over a decade: the effect of transition from conventional synthetic disease-modifying antirheumatic drugs to anti-tumour necrosis factor in patients with psoriatic arthritis. (20th September 2018) - Allard, Andrew; Antony, Anna; Shaddick, Gavin; Jadon, Deepak R; Cavill, Charlotte; Robinson, Graham; Korendowych, Eleanor; McHugh, Neil; Tillett, William
Abstract: Objectives: To describe the trajectory of radiographic progression among patients with PsA who transitioned from conventional synthetic DMARDs to anti-TNF-α inhibitors in routine care. Methods: A retrospective sample of patients with PsA (ClASsification criteria for Psoriatic ARthritis) was taken from the Bath longitudinal cohort. All patients had radiographs of the hands and feet taken: 5 years before (T0 ), at the time of (T1 ) and 5 years after (T2 ) commencing anti-TNF treatment. Radiographs were scored blinded using the PsA-modified Sharp-van der Heijde score (mSvdHS) and for osteoproliferation (Psoriatic Arthritis Ratingen Score) by A.Allard, A.Antony and W.T. This sample size was calculated to ensure 90% power to determine the smallest detectable difference of the mSvdHS to a 5% significance level. Cumulative probability plots were used to determine the probability of radiographic progression pre- (T0 –T1 ) and post- (T1 –T2 ) anti-TNF treatment. Results: Eighty-four radiographs from 28 patients were selected for inclusion. The median [interquartile range (IQR)] disease duration at baseline (T0 ) was 8.5 (0–19.5) years. The interval between T0 –T1 and T1 –T2 was 4.2 years (3.34–6.65) and 4.9 years (4.25–5.87), respectively. The median mSvdHS at baseline (T0 ) was 8.5 (IQR 1.75–27.5). The median (IQR) rate of change in mSvdHS per year reduced after commencing anti-TNF, from 2.1 (0.88–3.92) between T0 –T1 to 1.0 (IQR 0.05–2.35) between T1 –T2 ( P = 0.012). Conclusion: The trajectory of damage accumulation over a 10-year period in this observational clinical cohort is low overall. The rate of radiographic damage as measured by the mSvdHS slows following commencement of anti-TNF.